Does Anticoagulation Improve Flap Outcomes in Hypercoagulable Patients? A Systematic Review - Kotamarti, Vasanth S.; Shiah, Eric; Rezak, Kristen M.; Patel, Ashit; Ricci, Joseph A. (Journal of Reconstructive Microsurgery, 2020)
Background Despite improvements in microsurgical techniques, hypercoagulable patients remain a reconstructive challenge. Thrombophilias are a relatively common problem with potentially catastrophic results including free flap loss. The aim of this study was to assess the available literature on free tissue transfer in patients with known hypercoagulability to develop recommendations for management.Methods A systematic review of the PubMed, EBSCO, and Cochrane databases was performed in June 2018. Inclusion criteria were assessment of outcomes of free tissue transfer in patients with established hypercoagulability. Exclusion criteria were review articles, case reports, and studies lacking detailed discussion of anticoagulation regimens and surgical outcomes. Data collected included the number of hypercoagulable patients, anticoagulation regimens, thrombotic complications, flap success, and bleeding complications. Statistical analysis was performed using independent samples t-tests.Results Of 147 total results, four articles were included for analysis. One relevant article published after search completion was included. In total, 185 free tissue transfers were performed in 155 thrombophilic patients. Anticoagulation regimens varied widely but often included intraoperative continuous heparin, with or without additional bolus, followed by postoperative and outpatient anticoagulation. Hypercoagulable patients often developed late postoperative thromboses. Of the intraoperative thromboses, 36.4% were successfully salvaged. No flaps with postoperative thrombosis were salvaged. Preemptive therapeutic anticoagulation improved outcomes but increased the bleeding risk.Conclusion Free tissue transfer may be successful in hypercoagulable patients. High-risk patients identified preoperatively should receive therapeutic anticoagulation initiated intraoperatively unless contraindicated. Salvage after postoperative thrombosis is poor. Ultimately, the benefits of free tissue transfer must be considered with the potential morbidity of bleeding complications on a case-by-case basis when developing a reconstructive plan. Initiating anticoagulation based on the presence of intraoperative risk factors may prevent unnecessary intervention.
Keywords: anticoagulation; free flaps; hypercoagulable; systematic review